Randomized trial of labor induction in women 35 years of age or older - Walker, Kate F.; Bugg, George J.; Macpherson, Marion; McCormick, Carol; Grace, Nicky; Wildsmith, Chris; Bradshaw, Lucy; Smith, Gordon C.S.; Thornton, Jim (Massachusetts Medical Society, 2016)
BACKGROUND The risk of antepartum stillbirth at term is higher among women 35 years of age or older than among younger women. Labor induction may reduce the risk of stillbirth, but it also may increase the risk of cesarean delivery, which already is common in this older age group. METHODS We conducted a randomized, controlled trial involving primigravid women who were 35 years of age or older. Women were randomly assigned to labor induction between 39 weeks 0 days and 39 weeks 6 days of gestation or to expectant management (i.e., waiting until the spontaneous onset of labor or until the development of a medical problem that mandated induction). The primary outcome was cesarean delivery. The trial was not designed or powered to assess the effects of labor induction on stillbirth. RESULTS A total of 619 women underwent randomization. In an intention-to-treat analysis, there were no significant between-group differences in the percentage of women who underwent a cesarean section (98 of 304 women in the induction group [32%] and 103 of 314 women in the expectant-management group [33%]; relative risk, 0.99; 95% confidence interval [CI], 0.87 to 1.14) or in the percentage of women who had a vaginal delivery with the use of forceps or vacuum (115 of 304 women [38%] and 104 of 314 women [33%], respectively; relative risk, 1.30; 95% CI, 0.96 to 1.77). There were no maternal or infant deaths and no significant between-group differences in the women’s experience of childbirth or in the frequency of adverse maternal or neonatal outcomes. CONCLUSIONS Among women of advanced maternal age, induction of labor at 39 weeks of gestation, as compared with expectant management, had no significant effect on the rate of cesarean section and no adverse short-term effects on maternal or neonatal outcomes.